Cancer immunotherapy — immune checkpoint blockade and associated endocrinopathies - Byun, David J.; Wolchok, Jedd D.; Rosenberg, Lynne M.; Girotra, Monica (Nature reviews. Endocrinology, 2017)
Key Points The emergence of cancer immunotherapy has revolutionized cancer treatment but is associated with serious immune-related adverse effects (IRAEs) Cytotoxic T-lymphocyte antigen 4 (CTLA4)-targeted immunotherapy is associated with increased susceptibility to hypophysitis and primary thyroid dysfunction Programmed cell death protein 1 (PD1)-targeted immunotherapy is associated with primary thyroid dysfunction and type 1 diabetes mellitus CTLA4–PD1 combination therapy has an elevated incidence of hypothyroidism and possibly incidence rates of hypophysitis similar to those with monotherapy with CTLA4 antibodies IRAEs might be associated with improved clinical response of tumours to immunotherapy, but further studies are needed to evaluate this possible effect Targeting the immune system in tumour cells has become a central therapy for cancer treatment, but such drugs can lead to adverse effects. In this Review, the authors describe the immune-related endocrinopathies, such as hypophysitis, thyroid dysfunction and the development of diabetes mellitus that can result from cancer immunotherapy. Advances in cancer therapy in the past few years include the development of medications that modulate immune checkpoint proteins. Cytotoxic T-lymphocyte antigen 4 (CTLA4) and programmed cell death protein 1 (PD1) are two co-inhibitory receptors that are expressed on activated T cells against which therapeutic blocking antibodies have reached routine clinical use. Immune checkpoint blockade can induce inflammatory adverse effects, termed immune-related adverse events (IRAEs), which resemble autoimmune disease. In this Review, we describe the current data regarding immune-related endocrinopathies, including hypophysitis, thyroid dysfunction and diabetes mellitus. We discuss the clinical management of these endocrinopathies within the context of our current understanding of the mechanisms of IRAEs.